Effects of Inquiry Learning on Students' Science Process Skills and Critical Thinking: A Meta-Analysis - Laras Syahgiah; Aprina Maharani ZAN; Asrizal Asrizal (Journal of Innovative Physics Teaching, 2023)
The skills of a student are needed to achieve success in learning and everyday life. However, their skills were still low. Solution to solve this problem is to apply an inquiry learning model during learning. This research aims to determine the effect of the inquiry learning model on students' science process skills and critical thinking which is reviewed based on the level of education, subject matter and type of inquiry learning model. This type of research is a meta-analysis. Meta-analysis is research conducted by summarizing research data, reviewing and analyzing research data from several pre-existing research results. The articles of this research consisted of 20 articles that already had an ISSN. The instruments used were category codes and effect size calculations. The steps of meta analysis are conducting a literature review, collecting data, researching and assessing articles, analyzing and interpreting articles and compiling report results. The data analysis technique in this study is to calculate the magnitude of the effect using the   formula (1981) based on the mean, standard deviation, and t-test. From the data analysis carried out, it can be stated that four research results. First, the application of the inquiry learning model has a significant effect on science process skills and critical thinking skills based on level education, learning materials, and types of inquiry learning model.